The epistemological challenge of the “pedagogy of talents”: educating for resilience in order not to waste social capital - Falaschi, Elena (Studi sulla Formazione/Open Journal of Education, 2019)
After explaining the difference between “genius”, “talent” and “giftedness”, this paper highlights the educational aspect of the pedagogy of talents. The role and skills of teachers are crucial for the development of students’ individual potential, so that they can benefit from qualitatively differentiated programs within a truly inclusive school curriculum. As a matter of fact, the intellectually gifted subjects do not usually get their needs met, feeding disadvantages that require repairing educational interventions. Thus, talents that are not acknowledged, and therefore not developed, represent the greatest waste of potentially valuable resources, for the individual himself and for the entire society. The best way to protect talents from droping out of both school and society is a resilient recovery. Since drop out – understood as exclusion and loss – represents today an urgent cultural, political and educational problem, it is necessary to safeguard that positive “deviance” of thought, typical of talent, by planning and experimenting innovative actions of education for resilience.